IDENTIFYING PROFITABILITY DETERMINANTS IN THE HOTEL INDUSTRY PRE AND DURING THE COVID-19 PANDEMIC IN THE - Petkovska, Ivona; Trpkova-Nestorovska, Marija (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
This study aims to explore the impact of the current challenges that the hotel industry is experiencing with the COVID-19 pandemic. The empirical analysis identifies the key determinants that have a significant impact on the improvement of the current situation of the hotel industry. The paper elaborates the ongoing situation of the pandemic in the global service industry; Special attention is given of the pre-pandemic and in the pandemic situation in the hotel industry in North Macedonia. The present pandemic resulted in global challenges, especially affecting the economy and the healthcare system of different countries. It has also posed spillover effects on the global industries, including tourism and travel that nowadays are the major contributors to the service industry worldwide. Since tourism had a great impact on raising the economy in many countries, national economy included, this research main goal is to identify the determinants that have affected the hotel profits the most in this time of pandemic through the appropriate literature and theoretical background, and with empirical analysis. The analysis includes exploratory factor analysis, reliability analysis, and regression model. For this analysis, a data from 120 questionnaires were used. Management from different hotels from all parts of the country were interviewed. Revealing the main determinants that affect the improvement of the existing situation in the hotel industry could contribute to the improvement of the decision-making process in an emerging crisis environment. It can also trigger the most affected parts of the hotel businesses and point out to segments which need the most attention. Lessons learned can contribute to better preparation for similar risks in the future.
Keywords: tourism, firm performance, exploratory factor analysis